Analisis Efisiensi Kinerja Rantai Pasok Teh di PT Perkebunan Nusantara I Regional II Unit Sinumbra, Perkebunan Sinumbra Menggunakan Metode Data Envelopment Analysis (DEA) - Dewi, Mira Santika; Rahmah, Devi Maulida; Ardiansah, Irfan; Syahmurman, Faizal (Politeknik Negeri Lampung, 2025)
Regional II Sinumbra Unit is a state-owned company. Tea is a Superior commodity that has high export opportunities. PTPN I Regional II Sinumbra Unit is a state-owned company that maintains and processes black tea products. The production of black tea involves the performance of the supply chain of high-quality black tea products. The purpose of this study was to determine the efficiency value of the tea supply chain performance of the five regions in the Sinumbra Plantation. Data collection by interview and secondary data analysis on the head of the production, head of the field section, and several staff at PTPN I Regional II Sinumbra. The method used is the Data Envelopment Analysis (DEA) method with DEAP 2.1 software to analyze the efficiency of supply chain performance. Supply chain flows include goods, financial, and information flows. The results showed that region I afdeling II is an area that has high efficiency compared to the other five regions with an average of 0.689. Each region produces a fairly good efficiency value with an average vulnerability of 0.568-0.689.